2021
DOI: 10.3389/fnano.2021.777810
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine/β-Alanine Carbon Dots Use as DNA Carriers Into E. coli Cells

Abstract: Introducing foreign DNA into bacterial cells is essential in functional genomics and molecular research. Currently, heat shock and electroporation are the two major techniques of gene delivery in bacterial cells. However, both the techniques are time and resource consuming and are limited to a few species or strains of bacteria and there is a need to develop new transformation alternatives. Carbon dots with unique features such as facile synthesis, ease of functionalization, nontoxicity, and biocompatibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…The CDs without any surface modification showed 4.89% toxicity. On the other hand, CDs modified with PEI did not show any cytotoxicity against E. coli, which can be compared with the findings of Devkota et al [44], who synthesized…”
Section: Antibacterial Activity Of Synthesized Cdssupporting
confidence: 81%
See 1 more Smart Citation
“…The CDs without any surface modification showed 4.89% toxicity. On the other hand, CDs modified with PEI did not show any cytotoxicity against E. coli, which can be compared with the findings of Devkota et al [44], who synthesized…”
Section: Antibacterial Activity Of Synthesized Cdssupporting
confidence: 81%
“…The CDs without any surface modification showed 4.89% toxicity. On the other hand, CDs modified with PEI did not show any cytotoxicity against E. coli, which can be compared with the findings of Devkota et al [44], who synthesized amine-functionalized carbon dots with PEI and found no antimicrobial effect on bacterial species like Agrobacterium, Salmonella, Pectobacterium and E. coli. Hence, our study showed that doping with urea during CD synthesis contributed to favorable surface modifications in CDs and exhibited antibacterial properties when compared to other doping agents such as PEI and HMTA (Table 4).…”
Section: Antibacterial Activity Of Synthesized Cdssupporting
confidence: 79%
“…Extensive literature studies demonstrate that the CDs applied to gene delivery normally contain abundant amine groups resulting in CDs with positive surface charges, which promotes their binding to negatively charged nucleic acids by electrostatic interactions. 168 To prepare positively charged CDs, polyethylenimine (PEI), polyethylene glycol (PEG), polyethylene diamine (PAMAM), chitosan, and poly-L-lysine are frequently used as precursors or grafted on the surface of CDs. 169 Among them, PEI as a commercial transfection reagent is popular in the development of cationic CDs and gene delivery applications.…”
Section: ■ Carbon Dots In Nanomedicinementioning
confidence: 99%